2011
DOI: 10.4236/ijcm.2011.23046
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation with E-Cigarettes in Smokers with a Documented History of Depression and Recurring Relapses

Abstract: The association between nicotine dependence and affective disorders, particularly major depressive disorder (MDD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In surveys with non-probability samples, laboratory research and other case reports, the majority of reported side effects were minor, including mouth or throat irritation/dryness,42–44 53 cough,47 80 86 vertigo,43 53 headache43 47 53 and nausea 43 53. In three prospective trials in which smokers tried ENDS for 6 or 12 months, there were no serious adverse events 75–77.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In surveys with non-probability samples, laboratory research and other case reports, the majority of reported side effects were minor, including mouth or throat irritation/dryness,42–44 53 cough,47 80 86 vertigo,43 53 headache43 47 53 and nausea 43 53. In three prospective trials in which smokers tried ENDS for 6 or 12 months, there were no serious adverse events 75–77.…”
Section: Resultsmentioning
confidence: 97%
“…Although successful quitting was generally not associated with ENDS use in large surveys,58 61 68 74 in convenience sample surveys, focus groups, case studies and interviews with dedicated ENDS users, they often reported that using the product helped them quit smoking42–44 46–50 80 81 86 or significantly reduce tobacco use,42 44 48 often despite being heavy smokers or having failed quit attempts in the past 43 44 46 48–50 80 81 86. Unlike quitting smoking, reducing smoking may not represent a positive public health outcome, given that it may indicate dual use of ENDS and regular cigarettes.…”
Section: Resultsmentioning
confidence: 99%
“…Users report needing time to familiarise themselves with e-cigarettes to get satisfaction [21,32], and studies that have reported some of the highest blood nicotine levels associated with e-cigarette use were undertaken in experienced users [33]. We have attempted to address this by providing participants with detailed illustrated instructions of how to use e-cigarettes, and requiring that they try them for a week prior to embarking on their quitting attempt.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have been conducted that show promise for the potential of e-cigarettes as cessation aids [19-21], none have been adequately powered. As noted, a number of surveys of users suggest potential in this area, but to date, no randomised trials that evaluate the long- term efficacy e-cigarettes on abstinence, in smokers motivated to quit, have been completed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Swedish smokers who switch to a chewable form of smokeless tobacco (i.e., snuff) as a replacement for smoking show that the use of this product is associated with minimal health risks and reduced mortality from cardiovascular disease [34]. Recent research with electronic cigarettes, battery-operated products designed for the purpose of nicotine delivery has found them to be safe and effective in helping smokers remain abstinent [35][36][37].…”
Section: What To Do In Case Of Relapse? a Practical Algorithmmentioning
confidence: 99%